Evaluation method for crack resistance of laser cladding additive manufacturing material
By performing laser cladding additive manufacturing in the annular groove and measuring the crack rate, the problem of unreliable crack resistance evaluation results of laser cladding additive manufacturing materials in the prior art is solved, and the laser cladding additive manufacturing is realized Accurate assessment of material crack resistance.
Patent Information
- Application Number
- CN202411394672.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-08
AI Technical Summary
The existing laser cladding surface modified crack resistance evaluation method cannot effectively evaluate the crack resistance of laser cladding additive manufacturing materials, resulting in low reliability of evaluation results.
Using a crack resistance evaluation method for laser cladding additive manufacturing materials, laser cladding additive manufacturing is carried out in the annular groove to measure the crack rate of the cladding layer, combined with the design and material selection of the annular groove, the The crack resistance of the material is evaluated.
Reliable assessment of crack resistance of laser cladding additive manufacturing materials is achieved, the accuracy and reliability of evaluation results are improved, and crack resistance can be evaluated according to the crack rate of different metal materials.
Smart Images

Figure CN119246810A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for evaluating crack resistance, and in particular to a method for evaluating crack resistance of a laser cladding additive manufacturing material. Background Art
[0002] Laser cladding additive manufacturing technology is an efficient additive manufacturing method. The high energy of the laser beam is used to quickly melt the material and quickly solidify and crystallize it to form a tightly bonded cladding layer, and the integral component is formed by stacking the additive layer layer by layer. However, due to the rapid heating and cooling characteristics of laser cladding additives, cracks are easily generated, affecting the quality and service life of the cladding additive components. Laser cladding additive manufacturing is essentially different from traditional laser cladding surface modification, and there are large differences in molten pool composition, solidification path, temperature, and stress distribution, which directly affect the crack mechanism and crack resistance evaluation method. Most of the existing evaluation methods for crack resistance of laser cladding are aimed at laser cladding surface modification. If the evaluation method of laser cladding surface modification is directly used for the evaluation of laser cladding additive manufacturing materials, the reliability of the evaluation results is low. Summary of the invention
[0003] Purpose of the invention: The first purpose of the present invention is to provide a method for evaluating the crack resistance of laser cladding additive manufacturing materials with high reliability of evaluation results.
[0004] Technical solution: The present invention discloses a method for evaluating the crack resistance of laser cladding additive manufacturing materials, comprising the following steps:
[0005] S1: Select a metal sample made of a laser cladding additive manufacturing material to be evaluated, perform laser cladding on the surface of the metal sample to obtain a test cladding layer, measure and calculate the width of the test cladding layer, and use the width of the test cladding layer as the cladding width of the metal material;
[0006] S2: constructing a crack resistance evaluation device with an annular groove, wherein the material of the crack resistance evaluation device is the same as that of the metal sample in step S1, the width of the annular groove is consistent with the cladding width, and using the same cladding powder as in step S1, single-layer or multi-layer laser cladding additive manufacturing is performed along an annular track in the annular groove to obtain a cladding layer of the metal material as a laser cladding additive manufacturing material;
[0007] S3: Take the cross section of the cladding layer every θ° from the starting position of laser cladding, measure the total crack length and height of each cross section, calculate the individual crack rate of each cross section, and calculate the average of all individual crack rates as the final crack rate of the metal material;
[0008] S4: for the multiple laser cladding additive manufacturing materials to be evaluated, steps S1-S3 are repeated respectively under the same test conditions to obtain final crack rates of the multiple laser cladding additive manufacturing materials, and the final crack rates of the multiple laser cladding additive manufacturing materials are ranked.
[0009] Furthermore, the method of obtaining the cladding width in step S1 is: selecting multiple positions of the test cladding layer, measuring the width of each position respectively, calculating the average width of all sampling point positions and taking it as the cladding width.
[0010] Furthermore, the calculation formula of the individual crack rate in step S3 is:
[0011]
[0012] Furthermore, the θ° is divisible by 360°.
[0013] Furthermore, the metal sample needs to be cleaned with an acetone solution before laser cladding and before laser cladding in the annular groove.
[0014] Furthermore, during the laser cladding process in step S2, an inert gas is introduced as a protective gas.
[0015] Furthermore, the metal plate has a length of 80-150 mm, a width of 15-30 mm, and a thickness of ≥1 mm.
[0016] The crack resistance evaluation device includes a bottom plate, a substrate arranged at the top of the bottom plate and having a circular hole at the center, and a cylinder arranged at the center of the substrate and cooperating with the substrate and the bottom plate to form an annular groove. The depth of the annular groove can be adjusted by the thickness of the substrate and the cylinder, and the width of the annular groove can be adjusted by the diameter of the circular hole and the cylinder. The materials of the bottom plate, the substrate and the cylinder are the same as those of the metal sample.
[0017] Furthermore, the length of the bottom plate is 75-300mm, the width is 75-300mm, and the thickness is ≥2mm; the length of the base plate is 50-200mm, the width is 50-200mm, and the thickness is ≥2mm; the diameter of the circular hole is ≥20mm; the diameter of the cylinder is ≥10mm, and the thickness is ≥2mm.
[0018] Furthermore, mounting holes are provided around the base plate and at the center of the cylinder, and fasteners for connecting the bottom plate are provided at the mounting holes of the base plate and the cylinder.
[0019] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:
[0020] (1) The present invention aims at the crack resistance of materials in the process of laser cladding additive manufacturing. Laser cladding single-layer or multi-layer additive manufacturing is performed in the space of an annular groove. Unlike the evaluation method of laser cladding surface modification, no crack source is preset. Instead, the side wall of the annular groove exerts tensile stress on the solidified cladding layer to cause cracking, thereby evaluating the crack resistance of the material, which is highly targeted. By selecting different metal materials for laser cladding and measuring their crack rates, the crack resistance of laser cladding additive manufacturing of different metal materials can be evaluated, and the evaluation results are reliable.
[0021] (2) The crack resistance evaluation device of the present invention has a simple overall structure and is easy to operate during laser cladding. The dimensions of the substrate, cylinder and bottom plate can be flexibly set according to actual requirements. The depth of the annular groove can be adjusted by changing the thickness of the substrate and the cylinder, thereby achieving adjustment of the constraint degree. The deeper the annular groove, the greater the constraint degree of the cladding layer.
[0022] (3) The method for calculating the crack rate of the present invention is rigorous, accurate and convenient, and comprehensively considers the differences in crack rates at different sampling positions of the cladding layer in the annular groove, which is beneficial to improving the reliability of the crack resistance assessment results of laser cladding additive manufacturing. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a schematic structural diagram of the crack resistance evaluation device of the present invention. DETAILED DESCRIPTION
[0024] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.
[0025] Example 1
[0026] The method for evaluating crack resistance of laser cladding additive manufacturing materials described in the present invention comprises the following steps:
[0027] S1: Select a metal sample made of a laser cladding additive manufacturing material to be evaluated, clean the metal sample with acetone solution, remove water, oil, etc. on the surface of the metal sample, perform laser cladding on the surface of the metal sample, and introduce inert gas as a protective gas during the laser cladding process to obtain a test cladding layer, measure and calculate the width of the test cladding layer, and use the width of the test cladding layer as the cladding width of the metal material, select multiple positions of the test cladding layer, measure the width of each position respectively, calculate the average width of all sampling points and use it as the cladding width, preferably, select multiple positions for measuring the width at equal intervals. Preferably, the length of the metal sample is 80-150mm, the width is 15-30mm, and the thickness is ≥1mm. Among them, the cladding metal powder for laser cladding can be selected from composite powders (such as carbides, nitrides, etc.), copper-based alloy powders, titanium-based alloy powders, magnesium-based alloy powders, aluminum-based alloy powders, nickel-based alloy powders, and cobalt-based alloy powders.
[0028] S2: Build a crack resistance evaluation device with an annular groove 4. The material of the crack resistance evaluation device is the same as that of the metal sample in step S1. The width of the annular groove is consistent with the cladding width. Use acetone solution to clean the crack resistance evaluation device to remove water, oil and other stains on its surface. Use the same cladding powder as in step S1 to perform single-layer or multi-layer laser cladding additive manufacturing along an annular trajectory in the annular groove 4. During the laser cladding additive manufacturing process, an inert gas is introduced as a protective gas to finally obtain a cladding layer of the metal material as a laser cladding additive manufacturing material.
[0029] like Figure 1 As shown, the crack resistance evaluation device includes a bottom plate 3, a substrate 2 and a cylinder 1. A circular hole is opened at the center of the substrate 2, and the cylinder 1 is arranged at the center of the circular hole of the substrate 2. Mounting holes are opened around the substrate 2 and at the center of the cylinder 1. Fasteners for connecting the bottom plate 3 are arranged at the mounting holes of the substrate 2 and the cylinder 1, that is, the substrate 2 and the cylinder 1 are installed on the top of the bottom plate 3 through the mounting holes and the fasteners, so as to achieve a tight connection between the three and avoid thermal deformation of the device due to high energy during the laser cladding additive manufacturing process; in actual application, the tight connection between the three is not limited to the use of fasteners through the opening, and welding or one-piece forming of the device can also be considered; the circular hole, the bottom plate 3 and the cylinder 1 constitute an annular groove for laser cladding additive manufacturing. Preferably, the bottom plate 3 has a length of 75-300 mm, a width of 75-300 mm, and a thickness ≥2 mm, the substrate 2 has a length of 50-200 mm, a width of 50-200 mm, and a thickness ≥2 mm, the diameter of the circular hole is ≥20 mm, and the diameter of the cylinder 1 is ≥10 mm and the thickness is ≥2 mm.
[0030] The depth of the annular groove 4 can be adjusted by the thickness of the substrate 2 and the cylinder 1. The deeper the annular groove, the greater the restraint of the cladding layer. The width of the annular groove 4 can be adjusted by the diameter of the circular hole and the cylinder 1. The materials of the bottom plate 3, the substrate 2 and the cylinder 1 are the same as those of the metal sample.
[0031] S3: Take a cross section of the cladding layer every θ° from the starting position of laser cladding, preferably, θ° can be divided by 360°, measure the total crack length and height of each cross section, calculate the individual crack rate of each cross section, and calculate the average of all individual crack rates as the final crack rate of the material; wherein the calculation formula of the individual crack rate is:
[0032]
[0033] S4: for the various laser cladding additive manufacturing materials to be evaluated, repeat steps S1-S3 respectively under the same test conditions to obtain final crack rates of the various laser cladding additive manufacturing materials, and rank the final crack rates of the various laser cladding additive manufacturing materials. The laser cladding additive manufacturing material with a lower crack rate has a stronger crack resistance.
[0034] Example 2
[0035] In this embodiment, Ni60A powder is selected as cladding powder, and 304 stainless steel, 310 stainless steel and 316 stainless steel are used as materials of metal sample and crack resistance evaluation device respectively, so as to evaluate the crack resistance of different materials manufactured by laser cladding additive manufacturing.
[0036] Prepare metal samples corresponding to 304 stainless steel, 310 stainless steel and 316 stainless steel respectively, and use wire cutting to prepare metal samples for trial cladding of the three stainless steel materials. The length, width and thickness of the three metal samples are consistent. Y ) is 80mm, width (W Y ) is 20mm, thickness (H Y ) is 2mm.
[0037] Use acetone solution to clean the three metal samples to remove water and oil stains on the surface of the metal samples.
[0038] The laser cladding process was adopted, and the experimental parameters were set to 1.5kW laser power, 3mm / s scanning speed, and 18g / min powder feeding rate. During the laser cladding process, argon gas with a purity of 99.9999% was introduced as a protective gas, and the argon flow rate was 15L / min. Argon gas was continuously introduced for 10s before and after the start of laser cladding. A rectangular spot with a size of 5mm×5mm was moved to the starting position of laser cladding, and laser cladding was performed on three metal samples respectively. The test cladding length was 60mm to obtain a test cladding layer.
[0039] After the three metal samples have cooled down, the width of the test cladding layer is measured at three equal parts of each metal sample from the starting point of laser cladding. The average width of the test cladding layer of each metal sample is calculated based on the measured width (W p ), and the average width of the 304 stainless steel test cladding layer (W p1 ) is 11.5 mm, and the average width of the 310 stainless steel test cladding layer (W p2 ) is 13mm, the average width of the 316 stainless steel test cladding layer (W p3 ) is 12.4 mm. The width of the annular groove 4 (W a ) and the average width of the test cladding layer (W p )equal.
[0040] Continuing to use the wire cutting method, the corresponding crack resistance evaluation devices were prepared using three kinds of stainless steel materials, that is, three kinds of stainless steel bottom plates 3, substrates 2 and cylinders 1 were prepared. The length (Lz) of the three sets of substrates 2 was 100mm, the width (Wz) was 100mm, the diameter of the circular hole (Dz) was 30mm, and the thickness (Hz) was 3mm; the length (Ld) of the three sets of bottom plates 3 was 200mm, the width (Wd) was 200mm, and the thickness (Hd) was 200mm. d ) is 5 mm; and the diameter of cylinder 1 (D L ) and the width (W a ) is related to the diameter of the cylinder 1 used for 304 stainless steel (D L1 ) is 18.5 mm, and the diameter of the cylinder 1 used for 310 stainless steel (D L2 ) is 17 mm, and the diameter of the cylinder 1 used for 316 stainless steel (D L3 ) is 17.6 mm; the thickness of the three groups of cylinders 1 (H L ) are all 3 mm; in the three groups of evaluation devices finally formed, the depth of the annular groove 4 of the three groups of evaluation devices is all 3 mm, the width of the annular groove 4 made of 304 stainless steel is 11.5 mm, the width of the annular groove 4 made of 310 stainless steel is 13 mm, and the width of the annular groove 4 made of 304 stainless steel is 12.4 mm.
[0041] Through holes with a diameter of 5 mm were opened around the periphery of each group of substrates 2 and at the center of the cylinder 1, and M5 threaded holes were opened at positions corresponding to the through holes on the three groups of bottom plates 3. The three groups of bottom plates 3, substrates 2 and cylinders 1 were cleaned with acetone solution to remove water and oil stains. The substrates 2 and cylinders 1 were fixed to the corresponding bottom plates 3 with M5 bolts to obtain three groups of different stainless steel material crack resistance evaluation devices.
[0042] The experimental parameters of the laser cladding process are consistent with the trial cladding test. Move the 5mm×5mm rectangular spot to any starting point on the annular groove 4, and perform laser cladding according to the preset annular path. Cladding two layers in succession, after the first layer is clad, continue to clad the second layer along the same annular path. Under the action of the laser heat source, the Ni60A powder melts and is evenly clad on the surface of the three stainless steel materials, but due to the limitation of the side wall of the annular groove 4, the normal shrinkage process of the cladding layer is hindered, resulting in the generation and continuous expansion of cracks.
[0043] After the three groups of crack resistance evaluation devices were cooled, the cross-section of the cladding layer was cut every 60° along the starting position of the laser cladding, and the total crack length (Lc) and cross-section height (Hc) of the cross-section were measured. The individual crack rate of each cross-section was calculated based on the measured data, and the crack rate (δp ). According to calculations, the crack rate of 304 stainless steel is 58.6%, the crack rate of 310 stainless steel is 78.6%, and the crack rate of 316 stainless steel is 65.7%.
[0044] The crack rates of the three stainless steel materials under the same conditions were ranked and the crack resistance of the three stainless steel materials was evaluated. The results showed that 304 stainless steel>316 stainless steel>310 stainless steel, which achieved the evaluation of crack resistance of laser cladding additive manufacturing.
[0045] Example 3
[0046] In this embodiment, WC powder is selected as cladding powder, and 2024 aluminum alloy, 5083 aluminum alloy and 6061 aluminum alloy are used as materials of metal samples and crack resistance evaluation devices respectively to evaluate the crack resistance of different materials manufactured by laser cladding additive manufacturing.
[0047] Prepare metal samples corresponding to 2024 aluminum alloy, 5083 aluminum alloy and 6061 aluminum alloy respectively, and use wire cutting to prepare metal samples for trial cladding of the three aluminum alloy materials. The length, width and thickness of the three metal samples are consistent. Y ) is 150mm, width (W Y ) is 30mm, thickness (H Y ) is 3mm.
[0048] Use acetone solution to clean the three metal samples to remove water and oil stains on the surface of the metal samples.
[0049] The laser cladding process was adopted, and the experimental parameters were set as 3kW laser power, 6mm / s scanning speed, and 25g / min powder feeding rate. During the laser cladding process, argon gas with a purity of 99.9999% was introduced as a protective gas, and the argon flow rate was 15L / min. Argon gas was continuously introduced for 10s before and after the start of laser cladding. A rectangular spot with a size of 4mm×4mm was moved to the starting position of laser cladding, and laser cladding was performed on three metal samples respectively. The test cladding length was 120mm to obtain a test cladding layer.
[0050] After the three metal samples have cooled down, the width of each metal sample is measured at five equal parts from the starting point of laser cladding. The width of the test cladding layer is measured, and then the average width of the test cladding layer of each metal sample is calculated based on the measured width (W p ), and the average width of the 2024 aluminum alloy cladding layer (W p1 ) is 8.3 mm, and the average width of the 5083 aluminum alloy cladding layer (W p2 ) is 7.8 mm, and the average width of the 6061 aluminum alloy cladding layer (W p3) is 8.5 mm. The width of the annular groove 4 (W a ) and the average width of the test cladding layer (W p )equal.
[0051] Continuing to use the wire cutting method, three kinds of stainless steel materials were used to prepare corresponding crack resistance evaluation devices, that is, three kinds of aluminum alloy materials were prepared for the bottom plate 3, substrate 2 and cylinder 1. The length of the three sets of substrates 2 (L z ) is 200mm, width (W z ) is 200mm, the diameter of the circular hole (D z ) is 50mm, thickness (H z ) is 4mm; the length of the three sets of bottom plates 3 (L d ) is 300mm, width (W d ) is 300mm, thickness (H d ) is 6 mm; and the diameter of cylinder 1 (D L ) and the width (W a ) is related to the diameter of the cylinder 1 used for 2024 aluminum alloy (D L1 ) is 41.7 mm, and the diameter of the cylinder 1 used for the 5083 aluminum alloy (D L2 ) is 42.2 mm, and the diameter of the cylinder 1 used for 6061 aluminum alloy (D L3 ) is 41.5 mm; the thickness of the three groups of cylinders 1 (H L ) are all 4 mm; in the three groups of evaluation devices finally formed, the depth of the annular groove 4 of the three groups of evaluation devices is all 4 mm, the width of the annular groove 4 prepared by 2024 aluminum alloy is 8.3 mm, the width of the annular groove 4 prepared by 5083 aluminum alloy is 7.8 mm, and the width of the annular groove 4 prepared by 6061 aluminum alloy is 8.5 mm.
[0052] Through holes with a diameter of 8 mm were opened around the periphery of the substrate 2 of each group and at the center of the cylinder 1, and M8 threaded holes were opened at positions corresponding to the through holes on the three groups of bottom plates 3. The three groups of bottom plates 3, substrates 2 and cylinders 1 were cleaned with acetone solution to remove water and oil stains. The substrates 2 and cylinders 1 were fixed to the corresponding bottom plates 3 with M5 bolts to obtain three groups of different crack resistance evaluation devices.
[0053] The experimental parameters of the laser cladding process are consistent with the trial cladding test. Move the 4mm×4mm rectangular spot to any starting point on the annular groove 4, and perform laser cladding according to the preset annular path. Cladding two layers in succession, after the first layer is clad, continue to clad the second layer along the same annular path. Under the action of the laser heat source, the WC powder melts and is evenly clad on the surface of the three aluminum alloy materials, but the side wall of the annular groove 4 hinders the normal shrinkage of the cladding layer, resulting in the generation and continuous expansion of cracks.
[0054] After the three groups of crack resistance evaluation devices were cooled, the cross-section of the cladding layer was cut every 90° along the starting cladding position, and the total crack length (Lc) and cross-section height (Hc) of the cross-section were measured. The individual crack rate of each cross-section was calculated based on the measured data, and the crack rate (δp) of the three aluminum alloy materials was obtained by taking the average of the individual crack rates of each cross-section. After calculation, the crack rate of 2024 aluminum alloy is 46.5%, the crack rate of 5083 aluminum alloy is 36.8%, and the crack rate of 6061 aluminum alloy is 60.7%.
[0055] The crack rates of the three aluminum alloy materials under the same conditions were ranked and the crack resistance of the three aluminum alloy materials was evaluated. The results showed that 5083 aluminum alloy>2024 aluminum alloy>6061 aluminum alloy, which achieved the evaluation of crack resistance of laser cladding additive manufacturing.
Claims
1. A method for evaluating crack resistance of laser cladding additive manufacturing materials, characterized in that: The following steps are involved: S1: Select a metal sample made of a laser cladding additive manufacturing material to be evaluated, perform laser cladding on the surface of the metal sample to obtain a test cladding layer, measure and calculate the width of the test cladding layer, and use the width of the test cladding layer as the cladding width of the metal material; S2: constructing a crack resistance evaluation device having an annular groove (4), wherein the material of the crack resistance evaluation device is the same as that of the metal sample in step S1, the width of the annular groove (4) is consistent with the cladding width, and using the same cladding powder as in step S1, single-layer or multi-layer laser cladding additive manufacturing is performed along an annular track in the annular groove (4) to obtain a cladding layer of the metal material as a laser cladding additive manufacturing material; S3: Take the cross section of the cladding layer every θ° from the starting position of laser cladding, measure the total crack length and height of each cross section, calculate the individual crack rate of each cross section, and calculate the average of all individual crack rates as the final crack rate of the metal material; S4: for the multiple laser cladding additive manufacturing materials to be evaluated, steps S1-S3 are repeated respectively under the same test conditions to obtain final crack rates of the multiple laser cladding additive manufacturing materials, and the final crack rates of the multiple laser cladding additive manufacturing materials are ranked.
2. The method for evaluating crack resistance of laser cladding additive manufacturing materials according to claim 1, characterized in that: The method of obtaining the cladding width in step S1 is: selecting multiple positions of the test cladding layer, measuring the width of each position respectively, calculating the average width of all sampling point positions and taking it as the cladding width.
3. The method for evaluating crack resistance of laser cladding additive manufacturing materials according to claim 1, characterized in that: The calculation formula of the individual crack rate in step S3 is:
4. The method for evaluating crack resistance of laser cladding additive manufacturing materials according to claim 1, characterized in that: The θ° is divisible by 360°.
5. The method for evaluating crack resistance of laser cladding additive manufacturing materials according to claim 1, characterized in that: The metal sample must be cleaned with acetone solution before laser cladding and before laser cladding in the annular groove.
6. The method for evaluating crack resistance of laser cladding additive manufacturing materials according to claim 1, characterized in that: During the laser cladding process described in step S2, an inert gas is introduced as a protective gas.
7. The method for evaluating crack resistance of laser cladding additive manufacturing materials according to claim 1, characterized in that: The metal sample has a length of 80-150 mm, a width of 15-30 mm, and a thickness of ≥1 mm.
8. The method for evaluating crack resistance of laser cladding additive manufacturing materials according to claim 1, characterized in that: The crack resistance evaluation device comprises a bottom plate (3), a substrate (2) arranged at the top of the bottom plate (3) and having a circular hole at the center thereof, and a cylinder (1) arranged at the center of the substrate (2) and cooperating with the substrate (2) and the bottom plate (3) to form an annular groove (4), wherein the depth of the annular groove (4) can be adjusted by the thickness of the substrate (2) and the cylinder (1), and the width of the annular groove (4) can be adjusted by the diameter of the circular hole and the cylinder (1), and the materials of the bottom plate (3), the substrate (2) and the cylinder (1) are the same as those of the metal sample.
9. The method for evaluating crack resistance of laser cladding additive manufacturing materials according to claim 8, characterized in that: The bottom plate (3) has a length of 75-300 mm, a width of 75-300 mm, and a thickness of ≥2 mm; the base plate (2) has a length of 50-200 mm, a width of 50-200 mm, and a thickness of ≥2 mm; the diameter of the circular hole is ≥20 mm; the diameter of the cylinder (1) is ≥10 mm, and the thickness is ≥2 mm.
10. The method for evaluating crack resistance of laser cladding additive manufacturing materials according to claim 9, characterized in that: Mounting holes are provided around the base plate (2) and at the center of the cylinder (1), and fasteners for connecting to the bottom plate (3) are provided at the mounting holes of the base plate (2) and the cylinder (1).
Citation Information
Patent Citations
Evaluation method for crack sensitivity of metal material in additive manufacturing process
CN109507194A
Density measurement method for cladding layer obtained through laser cladding
CN109738332A
Method for evaluating crack resistance of laser cladding coating
CN114279785A
Evaluation method of laser cladding crack sensitivity
CN115932208A
Device and method for evaluating crack resistance of laser cladding material
CN116183862A
